The Effect of Increasing Human Capital Investment on Economic Growth and Poverty : A Simulation Exercise - Collin, Matthew; Weil, David (World Bank, Washington, DC, 2018)
This paper examines the dynamic responses of income and poverty to increased investment in the human capital of new cohorts of workers, using a quantitative macroeconomic model with realistic demography. Compared to a baseline in which the rate of human capital investment currently observed in every country remains constant, the paper examines two alternative scenarios: one in which each country experiences a rate of growth of human capital investment that is typical of what was observed in the decade ending in 2015, and one in which each country raises human capital investment at a rate corresponding to the 75th percentile of what was observed in the data. In the former, world GDP per capita is 5 percent higher than baseline in the year 2050, while the global rate of $1.90 poverty is 0.7 percentage points lower in that year. In the latter, world GDP per capita is 12 percent higher than baseline in 2050, while the rate of $1.90 poverty drops by 1.4 percentage points. These gains are concentrated in poor countries. The paper argues in the context of our model that investing in people is more cost effective than investing in physical capital as a means to achieve specified income or poverty goals.